Intracellular biopolymer productions using mixed microbial cultures from fermented POME - Salmiati; Ujang, Zaini; Salim, M. R.; Md. Din, Mohd. Fadhil; Ahmad, M. A. (IWA Publishing, 2007)
This study aimed to produce polyhydroxyalkanoates (PHAs) from organic wastes by mixed bacterial cultures using anaerobic-aerobic fermentation systems. Palm oil mill effluent (POME) was used as an organic source, which was cultivated in a two-step-process of acidogenesis and acid polymerization. POME was operated in a continuous flow anaerobic reactor to access volatile fatty acids (VFAs) for PHAs production. During fermentation, VFA concentration was produced in the range of 5 to 8 g/L and the COD concentration reduced up to 80% from 65 g/L. The VFA from anaerobic fermentation was then utilised for PHA production using a mixed culture in availability of aerobic bioreactor. Production of PHAs was recorded high when using a high volume of substrates because of the higher VFA concentration. Even though the maximum PHA content was observed at only 40% of the cell dried weight (CDW), their production and performance are significant in mixed microbial culture.